Clicking into Place: Interfacing Terminal Alkyne Biosynthesis with Polyketide Synthases. Issue 7 (July 2020) - Passmore, Munro; Jenner, Matthew
Abstract : Engineering polyketide biosynthesis to enable the production of diverse chemical structures is a major challenge at present. Utilising an established biosynthetic cassette for terminal alkyne production, Porterfield et al . applied docking domain and site-directed mutagenesis approaches to interface these enzymes with modular polyketide synthase (PKS) enzymes, yielding products with a bio-orthogonal handle.